PENGARUH PENERAPAN PENILAIAN DIRI (SELF ASSESSMENT) DALAM MEMBENTUK KEBIASAAN BERPIKIR PRODUKTIF (HABIT’S OF MIND) SISWA - Ratih Permana Sari; Sri Setiawaty (Center for Research and Community Service (LPPM) University of Abulyatama, 2017)
Balancing the mental and individual skills of individuals to learn about everything they want or need to do with their lives is one thing that matters for the real purpose of education. One effort that can be done is to train and develop students' productive thinking habits through an application of formative assessment that can monitor the development of students. This study aims to determine the effect of the application of self-assessment in the form of productive thinking habits of students applied to the subject matter of the colloidal system. The research method using quasi experiment with